1.Usuń nawiasy i wykonaj redukcję wyrazów podobnych:
a) 9y+5+(2y+3x-y)-10y
b) (3-4x²+5x)-(-3x+5x²+3)
c) (1/4x²-0,2y-3)-(-1/5y+0,25x²-3)
d) (4a²-3ab-0,1a)+(-14a²+2ab+0,1a)
2.Doprowadź do najprostrzej postaci wyrażenie.
a) 8x-(4x+6y-5)-(-5y+8x-2)
b)(2a+b)-(3a+6b-1)+a+4b
c) -(x²-2xy)-(xy-2x²+4)+3xy-x²
d) -3a-[6a-4b-(5a-5b)]
e) -6x-4y-[-(6x-2y-3x+y)-4x+12+10y]

DAM NAJLEPSZE:)

1

Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-01-29T16:25:35+01:00
1
a) 9y+5+(2y+3x-y)-10y=9y+5+2y+3x-y=10y+3x+5

b) (3-4x²+5x)-(-3x+5x²+3)=3-4x²+5x+3x-5x²-3=-9x²+8x

c) (1/4x²-0,2y-3)-(-1/5y+0,25x²-3)= ¼x²-0,2y-3+⅕y-0,25x²+3=0

d) (4a²-3ab-0,1a)+(-14a²+2ab+0,1a)=4a²-3ab-0,1a-14a²+2ab+0,1a= -10a²-ab


2.Doprowadź do najprostrzej postaci wyrażenie.
a) 8x-(4x+6y-5)-(-5y+8x-2)=8x-4x-6y+5+5y-8x+2=-4a-y+7

b)(2a+b)-(3a+6b-1)+a+4b= 2a+b-3a-6b+1+a+4b=-b+1

c) -(x²-2xy)-(xy-2x²+4)+3xy-x²= -x²+2xy-xy+2x²-4+3xy-x²=4xy-4

d) -3a-[6a-4b-(5a-5b)]=-3a-(6a-4b-5a+5b)=-3a-6a+4b+5a-5b=-4a-b

e) -6x-4y-[-(6x-2y-3x+y)-4x+12+10y]= -6x-4y-(-6x+2y+3x-y-4x+12+10y)= -6x-4y+6x-2y-3x+y+4x-12-10y=x-15y-12
2 3 2